Merci Suárez plays it cool - Medina, Meg (Candlewick Press, 2022)
Eighth grade brings big changes for Merci Suárez including a new haircut, more independence, and an unexpected new friendship. Merci has never been one of the popular kids, so she's surprised when Avery Sanders, who will probably be named captain of the soccer team since she can afford to go to fancy soccer camps, starts talking to her more often and not just as teammates on the field. She starts to wonder if she could be Avery's friend too, but during their class's weekend-long trip to St. Augustine, Merci must make a difficult decision, and when a tragedy occurs, she'll learn who her true friends are.